Relationship of dimensions of trauma exposure and related symptoms to fear of crime and appraisal of future risk. - McClurg, Lauren G. (My University, 2015)
The central aim of the study was to investigate the relationships between dimensions of exposure to trauma (frequency, recency, perceived severity and type), posttraumatic stress symptomatology (PTSS), Fear of Crime (FoC) and Appraisal of Future Risk (AFR). The central goal was to refine current understandings of how the nature of traumatic exposure impacts psychological functioning, with regard to symptomatic responses and on-going sense of safety in the world. A secondary interest was to explore whether symptomatic responses might, together with exposure, be predictive of FoC and AFR. A quantitative cross-sectional research design was used. Measures included the standard and an adapted version of the Traumatic Stress Schedule (TSS), the Impact of Event Scale-Revised (IES-R), the Fear of Crime measure, and an open-ended question relating to AFR. The sample comprised of 167 university students at the University of the Witwatersrand in Johannesburg. Statistical analyses included descriptive statistics, Pearson’s correlations and regression analysis, and thematic analysis was conducted on the one open ended question on AFR. The results indicated very high levels of exposure to trauma with over 90% of the sample reporting exposure to trauma and 67.9% reporting multiple exposure. At least one crime-related exposure was reported by 81% of the sample and 60% reported an exposure unrelated to crime. High levels of both recent and severe exposure were reported. Levels of PTSS in the sample were very high, with 42.5% reporting symptoms at levels of clinical concern. Both Fear of Crime and expectation of future traumatization were rather pervasive in the sample. Findings show support for relationships between exposure to trauma and PTSS, FoC and AFR, frequency of traumatization demonstrating the most strong and consistent effect on all three outcome variables. PTSS was not found to significantly mediate the relationships between exposure and FoC or AFR. Several broad themes emerged from participants’ descriptions around factors influencing AFR, including environmental risk and past traumatization, among others.